2021
DOI: 10.1093/sf/soab010
|View full text |Cite
|
Sign up to set email alerts
|

Race, Gender, Higher Education, and Socioeconomic Attainment: Evidence from Baby Boomers at Midlife

Abstract: This article investigates White, Black, and Hispanic men’s and women’s access and midlife labor market returns to college quality. To do so, we use data from the National Longitudinal Survey of Youth-1979 Cohort (NLSY-79), merged with college quality information from the Barron’s Admissions Competitiveness Index. Although prior research has investigated similar dynamics in access and returns to higher education, this work typically excludes Hispanics and does not assess enrollments at community colleges and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Comparing the last two models, we see that after accounting for racial differences in pre-college class and academic backgrounds, college quality has little independent explanatory power for the Black-White completion gap. This finding echoes previous studies showing that racial gaps in college quality are fully explained or reversed after differences in class and academic backgrounds are taken into account (e.g., Conwell and Quadlin 2022). In summary, the Black-White gap in bachelor’s completion is primarily a result of racial disparities in resources and skills formed before college entry.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Comparing the last two models, we see that after accounting for racial differences in pre-college class and academic backgrounds, college quality has little independent explanatory power for the Black-White completion gap. This finding echoes previous studies showing that racial gaps in college quality are fully explained or reversed after differences in class and academic backgrounds are taken into account (e.g., Conwell and Quadlin 2022). In summary, the Black-White gap in bachelor’s completion is primarily a result of racial disparities in resources and skills formed before college entry.…”
Section: Resultssupporting
confidence: 86%
“…These disparities are largely driven by race and class differentials in academic preparation. In fact, relative to White students, Black students with comparable class backgrounds and academic qualifications are more likely to attend the nation's most selective colleges and universities, thanks in part to affirmative action policies practiced by those institutions (Grodsky 2007;Ciocca Eller and DiPrete 2018;Conwell and Quadlin 2021). On the other hand, however, it has been found that relative to White students, Black students are also more likely to "undermatch," i.e., to enroll in a college that is less selective than the kind of colleges they would likely have been accepted to given their academic records (e.g., Bowen et al 2009).…”
Section: College As a Stratifiermentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Baby Boomers were the first demographic to experience widespread access to higher education, and as a result, many achieved high-profile positions in government, business, and the arts (Conwell & Quadlin, 2022). Moreover, Baby Boomers are renowned for their dedication to social and political causes, such as the civil rights movement, women's rights, and environmentalism, indicating a strong sense of activism and civic engagement.…”
Section: Baby Boomersmentioning
confidence: 99%
“…These disparities are largely driven by race and class differentials in academic preparation. In fact, relative to White students, Black students with comparable class backgrounds and academic qualifications are more likely to attend the nation's most selective colleges and universities, thanks in part to affirmative action policies practiced by those institutions (Grodsky 2007;Ciocca Eller and DiPrete 2018;Conwell and Quadlin 2021). On the other hand, however, it has been found that relative to White students, Black students are also more likely to "undermatch," i.e., to enroll in a college that is less selective than the kind of colleges they would likely have been accepted to given their academic records (e.g., Bowen et al 2009).…”
Section: College As a Stratifiermentioning
confidence: 99%